KELEMBAGAAN DALAM PENGELOLAAN SAMPAH UNTUK PENINGKATAN KEBERSIHAN DI KOTA BANDUNG - Raden Mohamad Mulyadin; Kuncoro Ariawan; Indah Bangsawan; Subarudi Subarudi; Mohammad Iqbal (Jurnal Analisis Kebijakan Kehutanan, 2023)
One  of  the  social  problems  facing  in  Bandung  City  (BC)  is  waste  problem  because  waste  production  and pollution  affect  not  only  the  aesthetics,  cleanness,  and  convenience  of  the  city,  but  also  people’s  health  and  the city  environment.  This  problem  rises  as  the  population  grows  that  produce  more  household  waste,  meanwhile, the  institution  of  waste  management  is  weak.    An  institution  is  an  organization  with  its  supporting infrastructure  such  as  regulation,  authority,  work  mechanism,  human  resources,  and  financial  system.  This  research  aims  to analyze  waste  management  in  BC  from  its  institutional  aspect.  The  data  from  selected  respondents  are  collected through questionnaire and depth interviews. The data were analyzed by using a qualitative descriptive method. The research revealed that the BC Government has to obligate UU No. 18/2008 by issuing local regulations and Mayor regulations related to waste management. PD Kebersihan established since 1985 has not optimally conducted and finally it is liquidated. The new cleanliness institution replacing PD Kebersihan should continue the previous good program and improve the less optimal program of waste management. It is hoped that Bandung Major has to set up a priority-scale of waste management program that is synergized with the medium term planning of Bandung City.